2019
DOI: 10.1111/odi.13208
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' clinical competency towards oral mucosal diseases: Results from a mystery shopper study

Abstract: ObjectivesTo investigate the clinical advices pharmacists would give to patients who present with various oral mucosal lesions.Subjects and MethodsOne hundred and twenty pharmacists in three major cities in the United Arab Emirates (UAE) were approached by senior dental students acting as mystery shoppers. Pharmacists were shown an image of one of four oral mucosal lesions representing candidosis, aphthous ulcer, erosive lichen planus and squamous cell carcinoma (SCC). Pharmacists' referral pattern and choices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…Generally, low referral rates were identified, 45,47,49,51 with pharmacy support staff less likely to refer than pharmacists 39,44‐47,50 . OTC medications or pharmacy products were commonly supplied, with or without a referral, across all the eight studies involving a potentially cancerous lesion, 39,45,47,49,51,58 particularly by pharmacy support staff in three studies 46,47,50 . However, one of these studies found a significantly higher number of doctor, not dental, referrals for a mystery shopper scenario after an educational event, supply of a decision protocol and information packs 58 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Generally, low referral rates were identified, 45,47,49,51 with pharmacy support staff less likely to refer than pharmacists 39,44‐47,50 . OTC medications or pharmacy products were commonly supplied, with or without a referral, across all the eight studies involving a potentially cancerous lesion, 39,45,47,49,51,58 particularly by pharmacy support staff in three studies 46,47,50 . However, one of these studies found a significantly higher number of doctor, not dental, referrals for a mystery shopper scenario after an educational event, supply of a decision protocol and information packs 58 …”
Section: Resultsmentioning
confidence: 99%
“…12,26,29,33,37,40,41 Pharmacy professionals generally responded to DOHC inquires by recommending OTC medications, oral health products or oral hygiene advice, with or without dentist or doctor referral. 27,29,33,35,37,[42][43][44] Few studies reported on the types of OTC medication provided or recommended, except for studies that involved mystery shoppers or case vignettes, 39,[44][45][46][47][48][49][50][51] or involved dental pain. 28,30,42,48,52,53 For example, pharmacists and dentists reported a similar pattern of recommending OTC analgesics for dental pain.…”
Section: Responding To Dohc Queriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Aunque existan restricciones legales en el rol de los farmacéuticos como indicadores y dispensadores de fármacos y/o tratamientos, existe un incremento en esta práctica. Esta situación se agrava, cuando aparte se realizan diagnósticos a partir de la breve historia relatada por el paciente 11 . En un estudio de 2014, se describió la intervención de estos profesionales en diagnósticos odontológicos, sobre todo ligados a odontalgias y úlceras bucales 12 .…”
Section: Discussionunclassified